Advanced Temperature Design for Dynamic Performance Enhancement of PEMFCs Under High Current Density (HCD) - Fengyang Cai; Shanshan Cai; Zhengkai Tu; Siew Hwa Chan (Advanced Science, 2025)
Abstract The dynamic performance of proton exchange membrane fuel cells (PEMFCs) under high current density (HCD) rapid loading is crucial for commercialization. This study introduces an advanced temperature difference (TD) design featuring an in‐plane temperature gradient. By reconstructing cooling channels, optimal temperature distribution across the upstream, midstream, and downstream regions achieves balanced water‐gas‐heat conditions, enhancing the dynamic response of PEMFCs under HCD loading. Various TD designs are investigated across a broad humidity range, innovatively focusing on key moments involving load initiation, transient voltage minimum (TVM), and steady‐state voltage (SSV). Comprehensive evaluations encompassing voltage response and energy consumption assess TD enhancements, while electrochemical impedance spectroscopy (EIS) and local current density monitoring further elucidate underlying mechanisms. Results show the positive temperature difference (PTD) design enhances hydration upstream and mitigates flooding downstream under low‐humidity conditions. Conversely, the negative temperature difference (NTD) design tends to dehydration upstream and flooding downstream. At RH = 35%, the PTD design increases TVM by 18.2%, decreases voltage undershoot (VU) by 12.5%, raises SSV by 5.67%, and enhances electricity output by 7%. As humidity increases, the positive effect of the PTD design gradually weakens, though it still benefits the current density distribution uniformity.